Digital Marketing Applications in the Retail Sector: A Systematic Mapping Study - Indiani, Dini; Ria Arifianti; Anang Muftiadi (Ilomata International Journal of Management, 2024)
This study investigates the trends, methods, research types, and focus areas of digital marketing applications in retail from 2018 to 2022. Through a systematic mapping of fifty articles, the study aims to identify key contributions by country, prevalent research methods, types, and focal areas. The analysis reveals an overall increase in publications over the period, with a notable decline in 2022. In 2021, the United States and the United Kingdom emerged as the leading contributors to research in this field. Quantitative methods and Validation Research were found to be predominant, with Solution Papers following. A significant focus of recent research has been on Social Media Marketing and Emerging Technologies. The study provides a thorough review of recent developments in digital retail marketing, laying the groundwork for future research advancements